Heat conducting member, heat dissipating housing, and method for manufacturing heat conducting member
A lightweight aluminum plate with controlled non-through holes addresses the challenge of insufficient heat dissipation in electronic device casings by enhancing thermal conductivity and heat dissipation, ensuring efficient performance of high-generating components.
Patent Information
- Application Number
- JP2020210385
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-18
- Publication Date
- 2024-12-18
- Estimated Expiration
- 2040-12-18
AI Technical Summary
Existing metal casings for electronic devices, such as smartphones and digital cameras, face challenges in providing both lightweight construction and high thermal conductivity, particularly with the increased heat generation from components like GPUs, leading to insufficient heat dissipation and reduced performance.
A lightweight aluminum plate with non-through holes on the substrate surface, having specific gravity of 2.00 or less, thermal conductivity of 100 W/mK or more in the depth direction, and a thermal diffusivity ratio of more than 1.1 times in the planar direction, along with controlled pore diameter and density, is used to enhance thermal conductivity and heat dissipation.
The solution provides a metal casing with excellent thermal conductivity and heat dissipation, maintaining lightweight properties while effectively managing heat generated by high-performance electronic components.
Smart Images

Figure 0007602365000001 
Figure 0007602365000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a metal housing for use as a housing for electronic devices such as smartphones and digital video cameras, and in particular to a metal housing for transferring heat generated by electronic components inside the housing. [Background technology]
[0002] Currently, magnesium alloys (AZ91D, etc.) are used for the heat dissipation housings of electronic devices such as smartphones and digital cameras because of their light weight and high strength. The thermal conductivity of this magnesium alloy is about 50-55 W / mK, which is not particularly high among metals, but it is used because its specific gravity is about 1.83, making it the lightest of all light metals.
[0003] On the other hand, the camera modules of these electronic devices use high-calculation GPUs that support 4K / 8K video, and the amount of heat generated is increasing compared to conventional models. Therefore, if the thermal conductivity of the housing is insufficient, the heat dissipation from the camera module will be insufficient, and the only solution is to lower the clock speed of the GPU, which will result in a decrease in the video playback speed, etc. For this reason, there is a demand for metal housings with low specific gravity and high thermal conductivity, such as magnesium alloys.
[0004] In response to these issues, Patent Document 1 and other publications disclose aluminum that is lightweight and made by mixing and heating aluminum (powder) with high thermal conductivity potential and an unfoamed precursor, but the random formation of voids results in a loss of thermal conductivity (heat dissipation) of the generated heat. In addition, the voids are connected to each other, and through-holes are formed on both sides of the plate, which is undesirable for use as a housing for electronic devices as it affects the airtightness. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2007-100176 A Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention provides a metal housing for electronic devices that is lightweight and has excellent thermal conductivity, and has an object to provide a metal housing that has excellent thermal conductivity and heat dissipation properties. [Means for solving the problem]
[0007] Specific means for solving the problems include the following aspects.
[0008] <1> The substrate is an aluminum plate having a plurality of non-through holes on a surface thereof, The specific gravity is 2.00 or less, A heat conductive member, wherein the thermal conductivity of the aluminum plate in the depth direction is 100 W / mK or more, and the ratio of the thermal diffusivity in the depth direction to the thermal conductivity in the planar direction of the aluminum plate is more than 1.1 times.
[0009] <2> The average pore size of the open surface is 10 μm to 600 μm, and the surface pore density is 1 / mm 2 More than 50 pieces / mm 2 The above, wherein the porosity is 26% or more. <1> The heat conductive member according to claim 1.
[0010] <3> The average plate thickness is 0.5 mm or more and 5.0 mm or less. <1> or <2> The heat conductive member according to claim 1.
[0011] <4> the above <1> ~ <3> 13. A heat dissipation housing using the heat conductive member according to any one of claims 1 to 12.
[0012] <5> the above <1> ~ <3> A method for producing a heat conductive member according to any one of the above claims, a film forming step of forming an aluminum hydroxide film on a surface of an aluminum substrate; a hole forming step in which a hole forming process is performed after the film forming step; a film removing step of removing the aluminum hydroxide film; The manufacturing method of claim 1, Effect of the Invention
[0013] According to one embodiment of the present invention, it is possible to provide a metal housing for electronic devices that is lightweight and has excellent thermal conductivity, and it is possible to provide a metal housing that has excellent thermal conductivity and heat dissipation properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] <Aluminum plate> The heat conducting member of the present invention is an aluminum plate having a plurality of blind holes on the substrate surface. The aluminum plate constituting the thermal conduction member is an aluminum plate characterized in that it has multiple blind holes formed on the substrate surface that extend vertically and in the depth direction, has a specific gravity of 2.00 or less, a thermal conductivity in the depth direction of 100 W / mK or more, and a thermal diffusivity in the surface direction that is more than 1.1 times that in the depth direction.
[0015] The aluminum plate has an average pore size of 10 μm or more and 600 μm or less on the open surface, and a surface pore density of 1 pore / mm 2 More than 50 pieces / mm 2 It is preferable that the thickness of the aluminum plate is less than or equal to 100 mm and the porosity is 26% or more. By satisfying these conditions, it is possible to provide an aluminum plate that has excellent thermal conductivity in the depth direction, thermal diffusivity in the surface direction, and light weight (low specific gravity).
[0016] The average hole diameter and average hole density of the open hole surface are calculated by photographing the surface of the aluminum plate at a magnification of 200 times using a high-resolution scanning electron microscope (SEM) from the open hole surface of the aluminum plate, extracting at least 20 through holes with a ring-shaped periphery in the obtained SEM photograph, reading the hole diameter, and calculating the average value as the average hole diameter. The hole diameter is measured by measuring the maximum value of the distance between the ends of the hole portion. That is, since the shape of the hole is not limited to a substantially circular shape, when the shape of the open hole portion is non-circular, the maximum value of the distance between the ends of the hole portion is taken as the opening diameter. Therefore, for example, even in the case of a hole having a shape in which two or more holes are integrated, this is regarded as one hole, and the maximum value of the distance between the ends of the hole portion is taken as the hole diameter. In addition, the average hole density is calculated by reading the number of holes in a 20 mm x 20 mm field of view in the SEM photograph and calculating it as the number per unit area.
[0017] From the viewpoints of thermal conductivity and strength of the aluminum plate, the average pore size is preferably from 10 μm to 600 μm, more preferably from 30 μm to 550 μm, and particularly preferably from 50 μm to 500 μm.
[0018] The average hole density is set at 1 hole / mm from the viewpoint of manufacturing cost and aluminum strength. 2 More than 50 pieces / mm 2 Less than 3 pieces / mm is preferable. 2 More than 40 pieces / mm 2 Less than 5 pieces / mm is more preferable. 2 More than 30 pieces / mm 2 The following are particularly preferred:
[0019] The hole shape in the depth direction of the aluminum plate of the present invention can be confirmed by photographing the fracture surface of the aluminum plate using a high-resolution scanning electron microscope (SEM) at a magnification of 500. If the hole shape is formed randomly in the depth direction, it is not preferable from the viewpoint of thermal conductivity in the depth direction.
[0020] Regarding the specific gravity, a commercially available specific gravity measuring device using the Archimedes method can be used, for example, specific gravity measuring kit AD-1653 manufactured by A&D Co., Ltd. can be used for the measurement.
[0021] From the viewpoint of light weight, the specific gravity is preferably 2.00 or less, more preferably 1.90 or less, and particularly preferably 1.85 or less. There is no particular lower limit to the specific gravity, but in the manufacturing method of the present invention, from the viewpoint of thermal conductivity, the specific gravity is preferably 1.50 or more.
[0022] The porosity is calculated by calculating the specific gravity using the following formula. Since the basic specific gravity of aluminum varies depending on its alloy components, values such as those in the "Aluminum Technology Handbook" compiled by the Japan Light Metal Association are used.
[0023] (Formula 1) Porosity (%) = Specific gravity ÷ Basic specific gravity of aluminum
[0024] From the viewpoints of machinability, strength, and light weight, the thickness of the aluminum plate of the present invention is preferably 0.5 mm to 5.0 mm, more preferably 0.8 mm to 4.0 mm, and particularly preferably 1.0 mm to 3.0 mm. For accurate thickness measurement, a "low pressure thickness gauge" conforming to JIS K 6250 manufactured by Teclock Co., Ltd. or the like is used.
[0025] By producing an aluminum plate having the hole shape described above, it is possible to provide an aluminum plate having a thermal conductivity in the depth direction of 100 W / mK or more and a thermal diffusivity in the surface direction that is more than 1.1 times that in the depth direction.
[0026] The thermal conductivity in the depth direction is calculated by measuring the thermal diffusivity using, for example, the laser flash method (Kyoto Electronics Manufacturing Co., Ltd.'s thermal conductivity measuring device LFA-502) or the temperature wave propagation phase difference method (Hitachi High-Technologies Corporation's ai-Phase Mobile M3), and then using the following formula. Note that the density and specific heat capacity of aluminum vary depending on its alloy components, so values from the "Aluminum Technology Handbook" compiled by the Japan Light Metal Association are used.
[0027] (Equation 2) Thermal conductivity (W / mK) = Thermal diffusivity (m 2 / s) × density (kg / m 3 ) × specific heat capacity (J / kgK)
[0028] The thermal diffusivity in the surface direction can be directly measured by a method such as the scanning laser heating AC method, and can be measured using an ULVAC LaserPIT-R or the like, and the ratio to the thermal diffusivity in the depth direction described above can be calculated.
[0029] The thermal diffusivity in the depth direction relative to the surface direction is preferably more than 1.1 times, more preferably more than 1.3 times, and more preferably more than 2.0 times, from the viewpoint of heat dissipation characteristics as a housing for a smartphone, digital video camera, etc. There is no particular upper limit to the ratio of thermal diffusivity in the surface direction to the depth direction, but from the viewpoint of dissipating heat from the GPU toward the surface direction of the housing, it is preferably 5.0 or less.
[0030] <Aluminum substrate> The aluminum base material used in the present invention is not particularly limited, and for example, a known aluminum base material described in JIS standard H4000 can be used. A6000 series aluminum having excellent strength, A1000 series aluminum having high thermal conductivity, etc. can be used appropriately depending on the characteristics of the electronic device, the design of the housing, etc.
[0031] <Aluminum sheet manufacturing method> Next, the method for producing the aluminum plate of the present invention will be described. The method for producing the aluminum plate of the present invention is a method for producing an aluminum plate having a plurality of non-through holes in the thickness direction, and includes a film forming step of forming an aluminum hydroxide film mainly composed of aluminum hydroxide on the surface of an aluminum base material, a hole forming step of performing a hole forming treatment in the depth direction after the film forming step, and a film removing step of removing the aluminum hydroxide film after the hole forming step.
[0032] In the electrolytic dissolution treatment for forming holes, a method is preferred in which a coating having a higher electrical resistivity than aluminum having a depression that can be the starting point of hole formation is first provided on the opening surface. As the coating having a higher electrical resistivity, an aluminum hydroxide film is preferably used from the viewpoint of ease of treatment. The aluminum hydroxide film has a higher resistivity than the aluminum substrate. Therefore, the holes formed in the aluminum substrate by the electrolytic dissolution treatment are formed in a shape with a maximum diameter inside, with the current being diffused more in the inner region than in the region in contact with the aluminum hydroxide film.
[0033] Here, since small holes are easily formed in the aluminum hydroxide film, non-penetrating holes that do not penetrate the aluminum base material are easily formed in the hole forming step. In other words, the above-mentioned recesses (starting points of hole formation) of 0.1 μm to 10 μm can be easily formed.
[0034] <Film formation process> In the present invention, the film forming step in the method for producing an aluminum sheet is a step of subjecting the surface of an aluminum base material to a film forming treatment to form an aluminum hydroxide film.
[0035] (Film formation treatment) The above-mentioned film forming treatment is not particularly limited, and for example, a treatment similar to a conventionally known aluminum hydroxide film forming treatment can be performed. For example, the conditions and devices described in paragraphs
[0013] to
[0026] of JP2011-201123A can be appropriately used as the film forming treatment.
[0036] In the present invention, the conditions for the film formation treatment vary depending on the electrolyte used and cannot be determined in general, but generally, the electrolyte concentration is 1 to 80 mass%, the solution temperature is 5 to 70°C, and the current density is 0.5 to 60 A / dm 2 The voltage is suitably 1 to 100 V and the electrolysis time is suitably 1 second to 20 minutes, and these are adjusted so as to obtain the desired coating amount.
[0037] In the present invention, it is preferable to carry out the electrochemical treatment using, as the electrolyte, nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid, oxalic acid, or a mixed acid of two or more of these acids. When carrying out the electrochemical treatment in an electrolyte containing nitric acid or hydrochloric acid, a direct current or an alternating current may be applied between the aluminum base material and the counter electrode. When a direct current is applied to the aluminum base material, the current density is 1 to 60 A / dm 2 It is preferable that the current is 5 to 50 A / dm 2 When the electrochemical treatment is carried out continuously, it is preferable to carry out the treatment by a liquid power supply system in which power is supplied to the aluminum base material via an electrolytic solution.
[0038] In the present invention, the amount of the aluminum hydroxide film formed by the film formation treatment is 0.05 to 50 g / m 2 It is preferable that the thickness is 0.1 to 10 g / m 2 It is more preferable that:
[0039] <Pore formation process> The hole forming step is a step of forming blind pores by performing an electrolytic dissolution treatment after the film forming step.
[0040] (Electrolytic dissolution treatment) The electrolytic dissolution treatment is not particularly limited, and may use direct current or alternating current, and may use an acidic solution as the electrolyte. Among them, it is preferable to carry out the electrochemical treatment using at least one acid selected from nitric acid and hydrochloric acid, and it is more preferable to carry out the electrochemical treatment using a mixed acid selected from at least one acid selected from sulfuric acid, phosphoric acid, and oxalic acid in addition to these acids.
[0041] In the present invention, as the acidic solution serving as the electrolyte, in addition to the above-mentioned acids, electrolytes described in the specifications of U.S. Pat. Nos. 4,671,859, 4,661,219, 4,618,405, 4,600,482, 4,566,960, 4,566,958, 4,566,959, 4,416,972, 4,374,710, 4,336,113, and 4,184,932 can also be used.
[0042] The concentration of the acidic solution is preferably 0.1 to 2.5% by mass, particularly preferably 0.2 to 2.0% by mass, and the liquid temperature of the acidic solution is preferably 20 to 80°C, more preferably 30 to 60°C.
[0043] The aqueous solution mainly made of the acid may be prepared by adding at least one of nitrate compounds having nitrate ions such as aluminum nitrate, sodium nitrate, and ammonium nitrate, hydrochloride compounds having hydrochloride ions such as aluminum chloride, sodium chloride, and ammonium chloride, and sulfate compounds having sulfate ions such as aluminum sulfate, sodium sulfate, and ammonium sulfate in a range of 1 g / L to saturation to an aqueous solution of the acid having a concentration of 1 to 100 g / L. The aqueous solution mainly made of the acid may also contain metals contained in aluminum alloys such as iron, copper, manganese, nickel, titanium, magnesium, and silica. It is preferable to use an aqueous solution of the acid having a concentration of 0.1 to 2 mass% to which aluminum chloride, aluminum nitrate, aluminum sulfate, or the like has been added so that the aluminum ions are 1 to 100 g / L.
[0044] In electrochemical dissolution treatment, a direct current is mainly used, but when an alternating current is used, the AC power wave is not particularly limited, and a sine wave, a square wave, a trapezoidal wave, a triangular wave, etc. can be used. Among them, a square wave or a trapezoidal wave is preferable, and a trapezoidal wave is particularly preferable.
[0045] (nitric acid electrolysis) In the present invention, an electrochemical dissolution treatment using an electrolyte containing nitric acid as a main component (hereinafter, also referred to as "nitric acid dissolution treatment") can be used to easily obtain a pore diameter of 10 μm or more and 600 μm or less and a surface pore density of 1 pore / mm 2 More than 50 pieces / mm 2 In this case, the nitric acid dissolution treatment is performed using a direct current and with an average current density of 5 A / dm because it is easy to control the dissolution point for forming the through holes. 2 or more, and the amount of electricity is 50C / dm 2It is preferable that the electrolytic treatment is carried out under the conditions of an average current density of 100 A / dm or more. 2 It is preferable that the quantity of electricity is 400000 C / dm 2 It is preferable that the electrolytic solution is equal to or lower than 0.5° C. The concentration and temperature of the electrolytic solution in nitric acid electrolysis are not particularly limited, and electrolysis can be performed at 30 to 60° C. using a high-concentration nitric acid electrolytic solution having a nitric acid concentration of, for example, 15 to 35% by mass, or at a high temperature of, for example, 80° C. or higher using a nitric acid electrolytic solution having a nitric acid concentration of, for example, 0.7 to 2% by mass. Electrolysis can also be performed using an electrolytic solution obtained by mixing the above-mentioned nitric acid electrolytic solution with at least one of sulfuric acid, oxalic acid, and phosphoric acid having a concentration of 0.1 to 50% by mass.
[0046] (Hydrogen electrolysis) In the present invention, a pore size average of 10 μm to 600 μm and a surface pore density of 1 pore / mm can be easily obtained by electrochemical dissolution treatment using an electrolyte solution mainly containing hydrochloric acid (hereinafter, also referred to as "hydrochloric acid dissolution treatment"). 2 More than 50 pieces / mm 2 or less, it is possible to form non-through pores having a porosity of 26% or more. Here, the hydrochloric acid dissolution treatment was performed using a direct current with an average current density of 5 A / dm because it was easy to control the dissolution point for forming the through holes. 2 or more, and the amount of electricity is 50C / dm 2 It is preferable that the electrolytic treatment is carried out under the conditions of an average current density of 100 A / dm or more. 2 It is preferable that the quantity of electricity is 400000 C / dm 2 It is preferable that the electrolytic solution is equal to or lower than 10° C. The concentration and temperature of the electrolytic solution in hydrochloric acid electrolysis are not particularly limited, and electrolysis can be performed at 30 to 60° C. using a hydrochloric acid electrolytic solution with a high concentration, for example, a hydrochloric acid concentration of 10 to 35% by mass, or at a high temperature, for example, 80° C. or higher, using a hydrochloric acid electrolytic solution with a hydrochloric acid concentration of 0.7 to 2% by mass. Electrolysis can also be performed using an electrolytic solution obtained by mixing at least one of sulfuric acid, oxalic acid, and phosphoric acid with a concentration of 0.1 to 50% by mass with the hydrochloric acid electrolytic solution.
[0047] <Coating film removal process> The film removal step is a step of removing the aluminum hydroxide film by carrying out a chemical dissolution treatment. In the film removal step, the aluminum hydroxide film can be removed by carrying out, for example, an acid etching treatment or an alkali etching treatment described below.
[0048] (acid etching treatment) The dissolution treatment is a treatment in which the aluminum hydroxide film is dissolved using a solution that preferentially dissolves aluminum hydroxide over aluminum (hereinafter referred to as an "aluminum hydroxide dissolving solution").
[0049] Here, the aluminum hydroxide dissolving solution is preferably an aqueous solution containing at least one selected from the group consisting of nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid, oxalic acid, chromium compounds, zirconium compounds, titanium compounds, lithium salts, cerium salts, magnesium salts, sodium silicofluoride, zinc fluoride, manganese compounds, molybdenum compounds, magnesium compounds, barium compounds, and simple halogens.
[0050] Specifically, examples of chromium compounds include chromium(III) oxide and anhydrous chromium(VI) acid. Examples of zirconium compounds include ammonium zirconate fluoride, zirconium fluoride, and zirconium chloride. Examples of titanium compounds include titanium oxide and titanium sulfide. Examples of lithium salts include lithium fluoride and lithium chloride. Examples of cerium salts include cerium fluoride and cerium chloride. Examples of magnesium salts include magnesium sulfide. Examples of manganese compounds include sodium permanganate and calcium permanganate. Examples of molybdenum compounds include sodium molybdate. Examples of magnesium compounds include magnesium fluoride pentahydrate. Examples of barium compounds include barium oxide, barium acetate, barium carbonate, barium chlorate, barium chloride, barium fluoride, barium iodide, barium lactate, barium oxalate, barium perchlorate, barium selenate, barium selenite, barium stearate, barium sulfite, barium titanate, barium hydroxide, barium nitrate, and hydrates thereof. Among the above barium compounds, barium oxide, barium acetate, and barium carbonate are preferred, and barium oxide is particularly preferred. Examples of halogen elements include chlorine, fluorine, and bromine.
[0051] Among them, the aluminum hydroxide dissolving solution is preferably an aqueous solution containing an acid, and examples of the acid include nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid, oxalic acid, etc., and may be a mixture of two or more acids. The acid concentration is preferably 0.01 mol / L or more, more preferably 0.05 mol / L or more, and even more preferably 0.1 mol / L or more. There is no particular upper limit, but generally it is preferably 10 mol / L or less, and more preferably 5 mol / L or less.
[0052] The dissolution treatment is carried out by contacting the aluminum substrate on which the aluminum hydroxide film is formed with the above-mentioned dissolving solution. The contact method is not particularly limited, and examples thereof include an immersion method and a spray method. Among these, the immersion method is preferred.
[0053] The immersion method is a treatment in which the aluminum substrate on which the aluminum hydroxide film is formed is immersed in the above-mentioned solution. Stirring during the immersion treatment is preferable because it ensures uniform treatment. The immersion treatment time is preferably 10 minutes or more, more preferably 1 hour or more, even more preferably 3 hours or more, and particularly preferably 5 hours or more.
[0054] (Alkaline etching treatment) The alkaline etching treatment is a treatment in which the aluminum hydroxide film is brought into contact with an alkaline solution to dissolve the surface layer.
[0055] Examples of the alkali used in the alkaline solution include caustic alkali and alkali metal salts. Specifically, examples of the caustic alkali include sodium hydroxide (caustic soda) and caustic potassium. Examples of the alkali metal salt include alkali metal silicates such as sodium metasilicate, sodium silicate, potassium metasilicate, and potassium silicate; alkali metal carbonates such as sodium carbonate and potassium carbonate; alkali metal aluminates such as sodium aluminate and potassium aluminate; alkali metal aldonic acid salts such as sodium gluconate and potassium gluconate; and alkali metal hydrogen phosphates such as sodium diphosphate, potassium diphosphate, sodium triphosphate, and potassium triphosphate. Among these, a caustic alkali solution and a solution containing both a caustic alkali and an alkali metal aluminate are preferred because of their high etching rate and low cost. In particular, an aqueous solution of sodium hydroxide is preferred.
[0056] The concentration of the alkaline solution is preferably 0.1 to 50% by mass, more preferably 0.2 to 10% by mass. When aluminum ions are dissolved in the alkaline solution, the concentration of the aluminum ions is preferably 0.01 to 10% by mass, more preferably 0.1 to 3% by mass. The temperature of the alkaline solution is preferably 10 to 90° C. The treatment time is preferably 1 to 120 seconds.
[0057] Methods for bringing the aluminum hydroxide film into contact with an alkaline solution include, for example, passing the aluminum base material on which the aluminum hydroxide film has been formed through a tank containing an alkaline solution, immersing the aluminum base material on which the aluminum hydroxide film has been formed in a tank containing an alkaline solution, and spraying the alkaline solution onto the surface of the aluminum base material on which the aluminum hydroxide film has been formed (aluminum hydroxide film). EXAMPLES
[0058] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention.
[0059] <Example 1> An aluminum substrate (A6061) having a thickness of 1.0 mm, a width of 200 mm, and a length of 150 mm was subjected to the treatments described below to prepare an aluminum substrate.
[0060] (Coating film formation process) A solution of nitric acid concentration 13.5 g / L and aluminum sulfate concentration 4.5 g / L was applied to the above aluminum substrate, and the aluminum substrate was used as the anode under the conditions of 52°C, direct current density 15 A / dm 2 was applied for 25 seconds to form an aluminum hydroxide film (film weight: 2.4 g / m) on one surface (one side) of the aluminum substrate. 2 After that, the substrate was washed with water by spraying.
[0061] (pore formation process) Next, using an electrolyte (nitric acid concentration: 13.5 g / L, aluminum sulfate concentration: 4.5 g / L) kept at 52°C, the aluminum substrate was used as the anode, and the total amount of electricity was 75,000 C / dm 2 The electrolytic treatment was carried out under the conditions of 2.6 A / dm2, and holes were formed in the depth direction from the oxide film surface of the aluminum substrate. The electrolytic treatment was carried out using a DC power source. The current density was 2.6 A / dm2. 2 Thereafter, the aluminum plate was washed with water by spraying and dried to prepare an aluminum substrate having holes.
[0062] (Coating removal process) Next, the aluminum base material after the electrolytic dissolution treatment was immersed in an aqueous solution (liquid temperature: 35°C) of 50.0 g / L sodium hydroxide and 5.0 g / L aluminum hydroxide for 3 seconds to dissolve and remove the aluminum hydroxide film. Thereafter, the aluminum plate was washed with water by spraying and dried to produce an aluminum plate of Example 1 having non-through holes. Details are shown in Table 1. In addition, to confirm the non-through hole structure, the aluminum plate was placed on a table-top viewer and optically confirmed to have a non-through structure.
[0063] <Examples 2 to 10 and Comparative Examples 1 to 5> Except for the changes shown in Table 1, aluminum plates or magnesium plates of Examples 2 to 10 and Comparative Examples 1 to 5 were produced in the same manner as in Example 1. Details are shown in Table 1.
[0064] [Measurement of the average pore size and pore density of the open surface] For the aluminum or magnesium plates prepared in Examples 1 to 10 and Comparative Examples 1 to 5, the pore diameters were measured in a field of view of 20 mm × 20 mm on the surface by photographing them with a high-resolution scanning electron microscope (SEM) at a magnification of 200 times, and the average value and number of pores were calculated. The average value was the average pore diameter [μm], and the number of pores per area was the pore density [holes / cm 2 The results are shown in Table 1.
[0065] [Measurement of specific gravity] The aluminum or magnesium plates produced in Examples 1 to 10 and Comparative Examples 1 to 5 were measured by Archimedes' method using a specific gravity measurement kit AD-1653 manufactured by A&D Co. The results are shown in Table 2.
[0066] [Thermal conductivity in the depth direction] The prepared aluminum or magnesium plates of Examples 1 to 10 and Comparative Examples 1 to 5 were measured by a laser flash method using a thermal conductivity measuring device LFA-502 manufactured by Kyoto Electronics Manufacturing Co., Ltd. The results are shown in Table 2.
[0067] [Thermal diffusivity in the depth direction relative to the surface direction] The thermal diffusivity in the depth direction of the aluminum or magnesium plates prepared in Examples 1 to 10 and Comparative Examples 1 to 5 was measured by the laser flash method using a thermal conductivity measuring device LFA-502 manufactured by Kyoto Electronics Manufacturing Co., Ltd. The thermal diffusivity in the surface direction was separately measured by the scanning laser heating AC method using a LaserPIT-R manufactured by ULVAC, Inc., and the ratio of the thermal diffusivity in the depth direction to the surface direction was calculated. The results are shown in Table 2.
[0068] [Thickness after hole formation process] The aluminum or magnesium plates prepared in Examples 1 to 10 and Comparative Examples 1 to 5 were measured using a low pressure thickness measuring device conforming to JIS K6250 manufactured by Techlock Co., Ltd. The results are shown in Table 2.
[0069] [Tensile strength] Measurement data was prepared for the aluminum or magnesium plates of Examples 1 to 10 and Comparative Examples 1 to 5 according to the provisions of JIS Z2201 "Tensile test pieces for metal materials." Then, using a metal tensile tester AG-Xplus made by Shimadzu Corporation, the elastic modulus (250-500N) [GPa], maximum point stress [N / mm 2 ], and 0.2% yield point stress [N / mm 2 The results are shown in Table 2.
[0070] The aluminum or magnesium plates of Examples 1 to 10 and Comparative Examples 1 to 5 were used as the "heat dissipation structure (400)" described in JP 2016-206364 A to check the light weight (specific gravity), operation clock property (thermal conductivity), and shut-out property against external contamination such as dust (non-through holes). As a result, Examples 1 to 10 showed better results than Comparative Examples 1 to 5.
[0071] [Table 1]
[0072] [Table 2]
Claims
1. The substrate is an aluminum plate having a plurality of non-through holes on a surface thereof, The specific gravity is 2.00 or less, A heat conductive member, wherein the thermal conductivity of the aluminum plate in the depth direction is 100 W / mK or more, and the ratio of the thermal diffusivity of the aluminum plate in the depth direction to the thermal diffusivity in the planar direction of the aluminum plate is more than 1.1 times.
2. A thermal conduction member as described in claim 1, wherein the average pore diameter of the open surface is 10 μm or more and 600 μm or less.
3. A thermally conductive member as described in claim 1 or 2, having a surface pore density of 1 pore / mm 2 or more and 50 pores / mm 2 or less.
4. The average pore size of the open surface is 10 μm or more and 600 μm or less, and the surface pore density is 1 pore / mm 2 More than 50 pieces / mm 2 The heat conductive member according to any one of claims 1 to 3, having a porosity of 26% or more.
5. The heat conductive member according to any one of claims 1 to 4, having an average plate thickness of 0.5 mm or more and 5.0 mm or less.
6. A heat dissipating housing using the thermally conductive member according to any one of claims 1 to 5.
7. A method for producing a heat conductive member according to any one of claims 1 to 5, comprising the steps of: a film forming step of forming an aluminum hydroxide film on a surface of an aluminum substrate; a hole forming step in which a hole forming process is performed after the film forming step; a film removing step of removing the aluminum hydroxide film; The manufacturing method of claim 1,
Citation Information
Patent Citations
Method for producing foamed aluminum
JP2007100176A
Method for producing fine structure, and fine structure
JP2007231336A
Heat radiator
JP2010268008A
Insulating reflection substrate and manufacturing method thereof
JP2013033956A
Three-dimensional composite thermal equilibrium radiator
JP3210737U
